Traffic Light Portable Menggunakan Rf Wireless dengan Sumber Energi Solar Cell - Rouhillah; Rachmad Ikhsan (Politeknik Aceh, 2022)
The Solar Cell Portable Traffic Light is fabricated in order to assist and facilitate the traffic during road work to avoid traffic jam and accident. It’a developed with microcontroller as the main controller, LED as the light (signal lamp), a pair of poles to wireless communication and solar panel and battery for the power source. The poles height is 3 meters, which can rovide the maximum distance about 100 meters in open are which yield comfort and safety for road users during road work.